PENERAPAN ANALISIS KORELASI KANONIK PADA HUBUNGAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH - PRABAWA, KADEK ANDREI; SUCIPTAWATI, NI LUH PUTU; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika, 2017)
Customer satisfaction is determined by the quality of customer service desired. Service quality of a company are important viewed from a consumer standpoint. The p